Teaching strategies and academic performance of students; Faculty of Chemical and Textile Engineering - UNI (Selecciones Matemáticas, 2021)
Objective: To know the level of association between the teaching strategies and the academic performance of the university students of the 4th year. cycle of the Faculty of Chemical and Textile Engineering (FIQT) of the National University of Engineering (UNI) considering the different subjects they are studying, corresponding to the year 2015. Materials and Method: It is a correlational study that considered as instruments a questionnaire and the report card to a sample of 100 students, whose data were processed in the SPSS program.Results: When applying Spearman’s Rho, the correlation coefficient is Rho = 0,410, which indicates that there is a moderate significant correlation between academic performance and teaching strategies, they have an impact on the educational quality of 4th cycle students the FIQT of the UNI in the 2015-2 cycle. Similarly, it was found that the dimension of the teacher teaching strategies variable (methodological strategies, management of educational resources, teacher performance and training, and content to be taught) are related to the variable academic performance, evidenced in the following relationship levels: Rho = 0,372, Rho = 0,163, Rho = 0,380 and Rho = 0,464. Conclusion: The teaching strategies of the teacher do have a certain relationship in the academic performance of the students, although not in a high proportion; This may be due to the fact that UNI students are well prepared, since the selection process to enter the university is very competitive.
Keywords: Strategies; teaching; academic performance